Analisis Kebijakan Indonesia Bekerja Sama dengan Jepang dalam Proyek Kereta Cepat Jakarta-Surabaya - Haryo Prasodjo; Najamuddin Khairur Rijal (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2021)
In 2015, Japan had to step down when Indonesia chose China in the 142.3 km Jakarta-Bandung fast train project. In 2016, the Government of Indonesia held a meeting with the Government of Japan, to discuss a project to continue the fast train, with the Jakarta-Surabaya route. Interestingly, the Jakarta-Surabaya fast train project was carried out directly without going through a tender process like the Jakarta-Bandung fast train project. Using an empirical rationality theory approach, this paper seeks to look at several factors behind the Indonesian government's policy of choosing Japan in the Jakarta-Surabaya semi-fast train project. Several aspects that will be examined in this research are, first, conditions and situations in Indonesia that require decision making. Second, Japan's commitment to Indonesia and the capacity and capability of Japan's fast train technology. Third, the various benefits obtained by Indonesia from the cooperation of the semi-fast train with Japan.